2017
DOI: 10.2320/matertrans.m2016310
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Quantum Chemical Studies of 1, 2, 3-Benzotriazole as Inhibitor for Copper and Steel in Simulated Tap Water

Abstract: The corrosion inhibition effect of benzotriazole on copper and steel in simulated tap water was investigated by using potentiodynamic polarization, electrochemical impedance spectroscopy and a quantum chemistry analysis. The corrosion inhibition ef ciency for copper and steel was accordingly increased with an increasing of the benzotriazole concentrations. However, the electrochemical test showed a signi cant difference between the inhibition ef ciency of copper and steel. From molecular theory and the adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…This could be due to the Cu–BTA complex formation, as BTA was adsorbed on the copper surface. Generally, the Cu–BTA complex formation acts as a mixed-type inhibitor to retard the oxidation of copper and reduction in oxygen [ 7 , 9 ]. The breakdown potential ( E b ) seen in the BTA-added specimens indicated that the Cu−BTA complex has an effective passive property [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This could be due to the Cu–BTA complex formation, as BTA was adsorbed on the copper surface. Generally, the Cu–BTA complex formation acts as a mixed-type inhibitor to retard the oxidation of copper and reduction in oxygen [ 7 , 9 ]. The breakdown potential ( E b ) seen in the BTA-added specimens indicated that the Cu−BTA complex has an effective passive property [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the Cu–BTA complex formation acts as a mixed-type inhibitor to retard the oxidation of copper and reduction in oxygen [ 7 , 9 ]. The breakdown potential ( E b ) seen in the BTA-added specimens indicated that the Cu−BTA complex has an effective passive property [ 9 ]. Notably, the Cu−BTA complex acts more effectively as an anodic corrosion inhibitor [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations